Vivendo em Pau Darco: interações e transformações sociais - Lívia Moreira Barroso (2018)
The aim of this thesis is to identify and analyze the possible transformations occurring in the media everyday and in the social interactions of the rural community of Pau D'arco, located in the hinterland of the interior of Piauí, from the installation of electricity through the Luz para Todos Program. We seek to understand the affectations caused by the insertion of a new media into the particular rural reality of the community, television, based on a relational perspective of communication. We also propose to perceive what remains and what changes in social relations, interactions, consumption habits, and how the narratives seen on television and radio are intertwined in the life of the local population. Our work starts from a case study of the reality of Pau D'arco, a specific rurality that is inserted within a context of massification, mediatization and modernity. For that, we use the concepts of territory and rural, understanding that we can not think of a homogeneous Brazilian rural, but a rural one that gains peculiarities in each space of Brazil - as is the case of the community studied. Our research shows that the community is undergoing a process of modernization, but continues to dialogue with the traditions; what is lived in Pau D'arco today can not be framed in closed definitions, but it constitutes a hybrid, constitutes a particular rural. It is perceived that there is a reconfiguration of relations, interactions, and electricity, together with the new media possibilities, particularly the arrival of television, have contributed to this. However, it is very evident that the dialogue with the television and the broader context brought by it is based on the experience and the repertoire lived / constituted by the residents, and that these are affirmative of the dynamics of the place. The methodology of analysis consists of the description and analysis of data collected in three phases of field research conducted between January 2017 and March 2018 - questionnaires, in-depth interviews and focus group. Based on the material raised by the field research, we constructed a narrative of the place, trying to interleave and stress the collected data (the characteristics of empiria) with the theoretical bases that deal with the rural, the processes of modernization and mediatization